2013
DOI: 10.5455/njppp.2013.3.53-56
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rational pharmacotherapy approach by medical students with and without Guide to Good prescribing guidelines

Abstract: Background: Knowledge of pharmacology forms the basis of rational pharmacotherapy practice. Teaching the medical students about systematic application of pharmacology in patients' care forms an essential component. It facilitates the medical students to develop a methodical approach in solving patients' clinical problems. Objective: To compare rational pharmacotherapy approach in management of essential hypertension and acute bronchial asthma by MBBS students before and after exposure to WHO GGP guidelines. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…This review also found that prescribing education interventions continue to be designed using the main concepts of the WHO GGP, demonstrating that despite its publication being back in 1994, the guideline continues to be the leading model for safe and rational prescribing to this day. This assertion is aided by the positive results yielded by interventions designed around the WHO GGP, both in assessment and student perception [28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This review also found that prescribing education interventions continue to be designed using the main concepts of the WHO GGP, demonstrating that despite its publication being back in 1994, the guideline continues to be the leading model for safe and rational prescribing to this day. This assertion is aided by the positive results yielded by interventions designed around the WHO GGP, both in assessment and student perception [28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Six case-based interventions were conducted through exposing students to treatment-setting standards from the World Health Organization (WHO) Guide to Good Prescribing (GGP) to varying [28][29][30][31][32][33]. Two studies used a combination of didactic lectures and subsequent prescription-writing for specific paper case scenarios [28,31], two studies implemented an individualised instruction approach where students were provided with the WHO GGP to use individually for creating treatment plans [32,33], one study used an experiential approach where students learned through observing real-life patients [30] and one study implemented the WHO GGP across an entire curriculum and in a variety of teaching formats [29]. Keisjers et al [29] made extensive use of the WHO GGP through incorporating it into a whole medical curriculum, where all pharmacology and pharmacotherapy modules were modelled according to the learning goals of the WHO GGP, and the guide was heavily featured during whole-group lectures, small-group tutorials and practical sessions.…”
Section: Interventions Designed Using and Featuring The Who Guide To mentioning
confidence: 99%
See 1 more Smart Citation
“…They should know how to prescribe safely and correctly and for this the skills, knowledge, and attitudes needed to make good prescribing decisions should be inculcated. 10,11 However, despite all the measures still irrational prescribing is prevalent in our country. It is better we make interns be aware of RUM and motivate them for the rational prescribing.…”
mentioning
confidence: 99%
“…Most of the articles published in the NJPPP were belong to the subjects like, Physiology [11,15,18,22-24,26-29,33,34,38-40,44,45,47,50,51,55] , Pharmacology [8,14,19,20,25,30,35,36,43,46,58] , Pharmacotherapeutics [5,17,21,31,54,57,59] and Pharmacy [7,53,56,60,62] . As the name of the journal itself contains the name of these particular subjects, it attracts the researcher of that field or work done in that field to be published in this journal.…”
Section: Discussionmentioning
confidence: 99%